Thermal comfort of different displacement ventilation systems in an aircraft passenger cabin. (January 2017) - Maier, Julia; Marggraf-Micheel, Claudia; Dehne, Tobias; Bosbach, Johannes
Abstract: Of current interest is the question whether ordinary mixing ventilation (MV) systems in an aircraft can be replaced by or combined with displacement ventilation (DV) systems without risking a decrease in thermal comfort. A reduction of energy consumption is a valuable gain. Three different versions of DV were analysed employing the Do 728 cabin test facility of the German Aerospace Center as cabin environment. Three human subject tests were carried out using 40 participants each: They aimed at analysing the thermal comfort of a) 100% DV, b) a 70:30% hybrid system combining DV and MV and c) a 50:50% hybrid system of DV and MV. Objective and subjective data were gathered to gain a differentiated image of the climate situation. Results were compared with results for MV that were obtained from an earlier study. Measurement data revealed a clear vertical temperature gradient for the DV systems; the relatively smallest temperature difference between feet and head was found for 100% DV and MV. Air velocity was lower in DV and increased with the amount of mixing ventilation that was provided. Regarding subjective sensations, thermal comfort was given in all three DV systems. The overall satisfaction with the climate tended to be highest in the 50:50 hybrid system. In summary, our results demonstrate that displacement ventilation can be used to provide a comfortable climate in an aircraft cabin. Known constraints of DV as e.g. large vertical temperature differences did not have any negative influence on climate comfort ratings of the passengers. Highlights: Thermal comfort of displacement ventilation (DV) in an aircraft cabin is analysed. Objective measurements are combined with the assessment of subjects' ratings. Usage of DV is advisable to implement a comfortable climate in aircraft cabins. Current standards may not be fully suitable for the evaluation of new DV systems.